Economic crisis accelerates urban structural change via inter-sectoral labour mobility - Daniel Straulino; Dario Diodato; Neave O'Clery (European Commission, Joint Research Centre (JRC), 2022)
Are recessions drivers of structural change? Here we investigate the resilience of cities, and argue that a re-allocation of labour between industrial sectors in times of crisis induces an acceleration in structural change. Using UK data, we find that cities experienced a sharp increase in inter-sectoral job transitions, and that local employment in skill-related sectors is most strongly associated with employment growth, during the recession, which we identify with the period of employment contraction between 2008 and 2011. This coincides with a massive but short-lived increase in the rate of structural change (i.e. the total change in employment shares of different industries) around 2009. These findings suggest that cities with skill-related sectors re-allocate workers in a crisis, thus inducing structural change.
Keywords: R11; R12; O14; J62; 330; Cities; resilience; financial crisis; labour markets; structural change; labour mobility